Seroprevalence and risk factors for Kaposi’s Sarcoma associated herpesvirus among men who have sex with men in Shanghai, China - Li, Yi; Zhang, Xingcan; Zhang, Yue; Wei, Minqi; Tao, Sijie; Yang, Ying (BMC infectious diseases, 2023)
This study aimed to facilitate the understanding of the transmission route and risk factors that might contribute to the infection of Kaposi's sarcoma associated herpesvirus (KSHV) among men who have sex with men (MSM). A cross-sectional study of 520 subjects was conducted in Shanghai, China in 2020. Plasma samples were collected and screened for KSHV, HIV, HBV, HCV, and syphilis. Univariate and multivariate logistic regression analyses were conducted to explore potential correlates of KSHV infection. The overall seroprevalence of KSHV was 43.8%, with an adjusted value of 29.8% according to the sensitivity and specificity of the KSHV screening assay. Individuals with lower levels of monthly income (Chi-sqaure = 4.11, P = 0.043) and more male sex partners (Chi-sqaure = 6.06, P = 0.014) were more likely to be infected with KSHV. Also, KSHV seropositivity was positively associated with being a student (aOR = 1.96; 95%CI: 1.09-3.61), being coinfected with HCV (aOR = 2.61; 95%CI: 1.05-7.10), and syphilis (aOR = 2.91; 95%CI: 1.30-6.89). The prevalence of KSHV in MSM remains high. As a risky sexual behavior, having multiple male sex partners is a key contributor to KSHV infection among this population. Efforts designed to control modifiable risk factors in order to reduce the burden of KSHV infection are indispensable. High KSHV seroprevalence among students MSM deserves more attention.